2010
DOI: 10.19030/ajbe.v3i10.484
|View full text |Cite
|
Sign up to set email alerts
|

Who And What Influences Choice Of University? Student And University Perceptions.

Abstract: <p class="MsoNormal" style="text-align: justify; margin: 0in 0.5in 0pt; mso-pagination: none;"><span style="color: black; font-size: 10pt;"><span style="font-family: Times New Roman;">Emerging peer-to-peer communication via social media, and the role of influential peers, is changing the way that marketers communicate with prospects.<span style="mso-spacerun: yes;">&nbsp; </span>The model is changing from a sender-receiver model to one that includes influential peer-to-peer an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
28
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 6 publications
9
28
1
Order By: Relevance
“…These items connect strongly to relationship marketing but are often ranked higher than in this study (fifth of nine) (Binsardi and Ekwulugo, 2003;Johnston, 2010).…”
Section: Opinionsmentioning
confidence: 51%
See 2 more Smart Citations
“…These items connect strongly to relationship marketing but are often ranked higher than in this study (fifth of nine) (Binsardi and Ekwulugo, 2003;Johnston, 2010).…”
Section: Opinionsmentioning
confidence: 51%
“…With increasing competition in higher education, universities face the challenge of recruiting sufficient students each year (Johnston, 2010) so understanding what influences student choice is very important to universities including those in Vietnam, though studies conducted within this specific context remain limited. This paper investigates the factors that influence Vietnamese students' choice of university in a context where the effects of globalization and education reform are changing higher education.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alvarado and López-Turley (2012) in their study found that the likelihood for Latinos and White students with college-oriented friends to apply to a four-year college or any college was high compared to students who did not have college-oriented friends. Friends do inform decisions about higher education institutions or potential schools, and courses selection (Brooks, 2003;Johnston, 2010;Alvarado & López-Turley, 2012). Although these studies were not related to MOOCs or other form of online education, they do shed some light on the findings of this study.…”
Section: Employment Statusmentioning
confidence: 80%
“…The high-income class students do not really consider cost much when deciding for a place to study. In his study on students and university perception, Johnston (2010) found that most students' choice was not influenced by the low cost of education but rather a multicultural diversity environment in the universities they were enrolled in among other factors; nevertheless, other students mention cost as not an influencing factor to them.…”
Section: Impact Of Costmentioning
confidence: 99%